PENINGKATAN KETERAMPILAN MENYUSUN WACANA NARASI MELALUI PENERAPAN PENDEKATAN EKLEKTIK - Sudaryanto, Sudaryanto (LPMPP Universitas Negeri Yogyakarta, 2001)
This research was aimed at improving the ability and skill of the student in Class 4A 1 inDepartment of Indonesia Education, Faculty of Language and arts, State University ofYogyakarta (KIP Yogyakarta) in developing texts in general, and specially narration in goodand correct Indonesian. It was expected that the students, then, would not find any difficultieswhen one day they had to write texts, especially those assigned by then lectures. The problemwas in this action research, that is, how effectiveness approach and tecnichque was used toimproving ability and skill of the students in developing narration texts. This problem wasdoing that, because in the beginning condition was known that students were still low to writeabout those texts.This classroom action research was comes out by applying was constructed an actionprogrammed, and it was divided into four cycles, and each cycle consisted of three steps oraction. Therefore, each cycle consisted of twelve steps or teaching-learning processes, and thenumber of the whole action was 12 times. The training for developing the texts was carried outby applying an approach eclectic or technique eclectic, those are it consisted several approachesand techniques. The approach was applied: integrative approach, practicum approach, anddemocratic approach, approach that gave attention to student's need. Mean while, the strategyor technique were applied: talkative technique, discussion technique, giving task technique,feedback technique, and cross correction technique.The result of the action research were: the first the actions carried out for developingnarration texts could improve the ability and skill of the students in developing texts, especiallythe narration texts. This could be seen from the data that out of 18 students, only two studentscould develop narration texts. After the action, all of them could develop narration texts.second: the approachesltechnique used in the action could improve the ability and the skill ofthe students in developing narration. Conclusion of this action research, that is the is ability andskill students to wrote narration texts were improve with the classroom action research.